Contemporary art, world cinema, and visual culture : essays - Dabashi, Hamid, 1951- (Anthem Press, 2019)
"The volume contains the collection of essays on modern and contemporary arts by Hamid Dabashi, the acclaimed cultural critic and scholar of Middle Eastern history and culture. It reintroduces the work of one theorist of modern and contemporary arts to extrapolate more universal issues of concern to art criticism in general"--